Government Employment and Pay : Some International Comparisons - Tait, Alan (Occasional Papers; Occasional Paper ;, 1983)
How many people are employed by the government? How many are employed by the central government compared with the state and local authorities? How many are employed in public enterprise? How much are they all paid? How much are they paid relative to each other, or relative to the private sector? Such questions interest people in general and economists and policymakers in particular; yet it is remarkable how little information is readily accessible on thes topics.